Study on the Seeds Germination and Biochemical Parameters (Chlorophyll, Proline, and Ascorbic Acid) of Soybean & Chickpea under the Influence of Heavy Metal (CD) Stress - Khan, Ruhi; Gulafshan; Rehman, Farha; Khan, Aabshar (International Journal of Scientific Research in Biological Sciences, 2020)
In the world population, the industrial & environmental pollution, and chemical toxicity raising. High speed industrialization and urbanization processes has show to the synthesis of pollutants such as pesticides, salt , petroleum products, acids and heavy metals in the natural resources. These pollutants affects both plants and animals. Heavy metals as well as lead, nickel, cadmium, copper, and mercury are important environmental factors that cause toxic effects on plants and animals. Here , we are study about Cadmium (Cd). It is possess dangerous threats on the agro-ecosystems. Cd act as a poisonous effect on the physiology of plants. In this review, we have summarized the effects of different concentrations (0, 100 ppm, 200 ppm ,and 400ppm) of heavy metal (Cd) on germination process of seeds and biochemical parameters i.e., (chlorophyll, proline, and ascorbic acid) of soybean & chickpea. In our experiment the data revealed that higher concentration (200ppm) of Cd increase the levels of proline and ascorbic acid, but decrease the chlorophyll content in leaf of soybean & chickpea plant. While this report exist on , heavy metal (Cd) act as stress for plants life , and how plants responses to overcome. The future scope of this work remains in dig out the signaling mechanisms in germinating seeds in response to any heavy metal stress.